Melatonin-induced Bacillus tequilensis enhanced the disease resistance of Camellia oleifera against anthracnose by modulating cell wall and phenylpropanoid metabolism - Zhou, Aiting; Zhou, Huiqin; Peng, Ruiqi; Liu, Di; Wu, Jianrong; Deng, Jia; Wang, Fang (Frontiers in Plant Science, 2025)
IntroductionAnthracnose poses a significant threat to the sustainable development of the Camellia oleifera industry. In this study, we aimed to assess the efficacy of melatonin-induced Bacillus tequilensis DZY6715 (MT-DZY 6715) in controlling C. oleifera anthracnose caused by Colletotrichum siamense.MethodsThe antifungal activity of MT-DZY6715 against C. siamense was systematically evaluated in vitro dual-culture assays and in planta infection trials. Furthermore, we analyzed the impact of MT-DZY 6715 on the anatomical features of C. oleifera leaves using histological sectioning. Additionally, transcriptome and enzymatic assays were employed to assess the expression of secondary metabolism-related genes and the activity of cell wall-degrading enzymes.ResultsThe application of MT-DZY 6715 effectively controls the growth of C. siamense, markedly reducing the incidence of C. oleifera anthracnose and delaying the spread of pathogens on the leaves. Furthermore, MT-DZY 6715 treatment enhanced leaf thickness, palisade mesophyll, as well as elevated the ratio of palisade mesophyll to spongy mesophyll (PS) and tissue compactness (CTR), while simultaneously decreasing tissue looseness (SR). Meanwhile, the leaf stomata undergo a reduction in size and a decrease in their openness. In addition, MT-DZY 6715 promoted the expression of secondary metabolism-related genes, such as PAL, CAL, Laccase, HCT, and CHI, and inhibited the activity of enzymes related to cell wall degradation (pectinase and cellulase), thereby coordinating and enhancing the accumulation of secondary metabolites and strengthening the mechanical properties of the cell wall.DiscussionThe results of this study demonstrate that MT-DZY 6715 enhances the resistance of C. oleifera to anthracnose by modulating leaf morphology, regulating stomatal function, and promoting the accumulation of secondary metabolites. These findings provides a scientific foundation for deploying MT-DZY6715 as an eco-friendly alternative to chemical fungicides in anthracnose management.